Quantitative trait locus mapping for seed mineral concentrations in two Arabidopsis thaliana recombinant inbred populations - Waters, Brian M (The New phytologist, 2008)
Biofortification of foods, achieved by increasing the concentrations of minerals such as iron (Fe) and zinc (Zn), is a goal of plant scientists. Understanding genes that influence seed mineral concentration in a model plant such as Arabidopsis could help in the development of nutritionally enhanced crop cultivars. Quantitative trait locus (QTL) mapping for seed concentrations of calcium (Ca), copper (Cu), Fe, potassium (K), magnesium (Mg), manganese (Mn), phosphorus (P), sulfur (S), and Zn was performed using two recombinant inbred line (RIL) populations, Columbia (Col) x Landsberg erecta (Ler) and Cape Verde Islands (Cvi) x Ler, grown on multiple occasions. QTL mapping was also performed using data from silique hulls and the ratio of seed:hull mineral concentration of the Cvi x Ler population. Over 100 QTLs that affected seed mineral concentration were identified. Twenty-nine seed QTLs were found in more than one experiment, and several QTLs were found for both seed and hull mineral traits. A number of candidate genes affecting seed mineral concentration are discussed. These results indicate that A. thaliana is a suitable and convenient model for discovery of genes that affect seed mineral concentration. Some strong QTLs had no obvious candidate genes, offering the possibility of identifying unknown genes that affect mineral uptake and translocation to seeds